Ecology and classification of North American Freshwater invertebrates - Thorp, James | Covich, Allan P (Estados Unidos | ESTADOS UNIDOS Academic Press / New York, 1991)
Contents: Introduction to freshwater invertebrates; An overview of freshwater; Protozoa; Porifera; The freshwater cnidaria coelenterates; Flatworms, turbellaria and nemertea..
Sin Especificar
Keywords: Invertebrados de agua dulce-Ecología-América del Norte | Invertebrados de agua dulce-Clasificación